2014
DOI: 10.1098/rspb.2013.2980
|View full text |Cite
|
Sign up to set email alerts
|

The geography and ecology of plant speciation: range overlap and niche divergence in sister species

Abstract: A goal of evolutionary biology is to understand the roles of geography and ecology in speciation. The recent shared ancestry of sister species can leave a major imprint on their geographical and ecological attributes, possibly revealing processes involved in speciation. We examined how ecological similarity, range overlap and range asymmetry are related to time since divergence of 71 sister species pairs in the California Floristic Province (CFP). We found that plants exhibit strikingly different age-range cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
283
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(303 citation statements)
references
References 93 publications
14
283
4
2
Order By: Relevance
“…genetic drift, mutations) or by divergent selection [2,25]. Longer periods of isolation are expected to increase ecological differentiation/divergence [26,27], and this has been demonstrated in several taxa [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…genetic drift, mutations) or by divergent selection [2,25]. Longer periods of isolation are expected to increase ecological differentiation/divergence [26,27], and this has been demonstrated in several taxa [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to reconstructing geographic modes of speciation, such as the proportion of sympatric sister species (e.g. (Phillimore et al 2008, Schnitzler et al 2011, Anacker and Strauss 2014, Cardillo and Warren 2016 , Cardillo & Warren 2016), are based only on shallow phylogenetic divergences and may be more sensitive to changes in overlap patterns that result from accounting for habitat loss in SDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Age-Range Correlation, for example, is based upon analysis of the overlap in species' distributions with respect to their divergence times (e.g. (Phillimore et al 2008, Schnitzler et al 2011, Anacker and Strauss 2014, Cardillo and Warren 2016 . In our analysis, we found that SDM models accounting for habitat loss increased the estimated degree of overlap among species, but did not appreciably alter the intercept or slope of the ARC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mudanças estruturais são esperadas em redes ecológicas a partir de eventos de especiação porque processos de diversificação de espécies modificam de forma simultânea múltiplos atributos do ambiente biótico (Schluter 2000;Nosil 2012). De fato, a reorganização das interações ecológicas nas espécies emergentes frequentemente modificará a amplitude e sobreposição de suas dimensões bióticas do nicho (Anacker & Strauss 2014), uma vez que a divergência adaptativa em traços mediadores de interações ecológicas possibilita a coexistência das espécies irmãs (Schluter 2000).…”
Section: Especiação Reorganização Do Nicho E Estabilidadeunclassified